Epigenetic control of gene function in schistosomes: a source of therapeutic targets? - Cabezas-Cruz, Alejandro (2014)
Université de Lille. Institut National de la Santé et de la Recherche Médicale. Centre National de la Recherche Scientifique. Institut Pasteur de Lille. Center for Infection and Immunity of Lille. Lille, France